Are private hospital emergency departments in Australia distributed to serve the wealthy community? - Mazen Baazeem; Estie Kruger; Marc Tennant (Wiley, 2024)
Abstract Objective This study investigates the geographical distribution of private hospitals in Australian capital cities in relation to the Index of Relative Socioeconomic Disadvantage. Methods Using Geographic Information System analysis, the study examined how private hospitals are distributed across different socioeconomic quartiles, providing a comprehensive visualisation of health care accessibility. Results The results indicate an unequal distribution with a substantial concentration of private hospitals within the vicinity of communities classified in the highest socioeconomic classification. This raises significant concerns about health care equity, particularly in light of the increased strain on health care systems before, during and after the COVID‐19 pandemic. Conclusions This study underscores the need for targeted policy interventions to enhance the resilience and accessibility of the private health care sector, specifically targeting disadvantaged communities. It suggests that comprehensive, geographically‐informed data is crucial for policymakers to make informed decisions that promote health equity in the postpandemic landscape.